The application of English Law in west Malaysia: Section 3 and 5 of the Civil Law act 1956 (revised 1972) / Zaharah Hussain Naser - Hussain Naser, Zaharah (Faculty of Law, 1987)
An interesting question which has given rise to a certain amount of discussion in the extent to which Malaysian Courts can adopt English law. Sections 3 and 5 of the Civil Law Act (Revised 1972) allow the courts to apply English law in certain circumstances but the exact scope of the provisions is far from clear. The main objectives of this project paper is to study how far Engl1sn law is applicable in West Malaysia as stated under Sections 3 and 5 of the Civil Law Act, 1956 (Revised 1972). Hopefully this project paper will make the readers understand that the English law is not totally applicable in the Malaysian Courts. There are certain limitations to the reception of English law which will be explored on this paper. According to the schematic outline of the study, Chapter 2 will discuss the English occupation and the introduction of English law in West Malaysia before 1956. This chapter mentions the history of the Straits Settlements and the Malays States before 1956 and how the British had introduced the English laws in these territories. A discussion of section 3 and 5 of the Civil Law Act, 1956 (Revised 1972) will be in Chapter 3. It includes the argument of Professor G.w. Bartholomew and Joseph Chia.